The Gradience of Multilingualism in Typical and Impaired Language Development: Positioning Bilectalism within Comparative Bilingualism - Grohmann, Kleanthes K.; Kambanaros, Maria (Frontiers in Psychology, 2016)
A multitude of factors characterizes bi- and multilingual compared to monolingual language acquisition. Two of the most prominent viewpoints have recently been put in perspective and enriched by a third (Tsimpli 2014): age of onset of children’s exposure to their native languages, the role of the input they receive, and the timing in monolingual first language development of the phenomena examined in bi- and multilingual children’s performance. This article picks up a fourth potential factor (Grohmann 2014b): language proximity, that is, the closeness between the two or more grammars a multilingual child acquires. It is a first attempt to flesh out the proposed gradient scale of multilingualism within the approach dubbed ‘comparative bilingualism’. The empirical part of this project comes from three types of research: (i) the acquisition and subsequent development of pronominal object clitic placement in two closely related varieties of Greek by bilectal, binational, bilingual, and multilingual children; (ii) the performance on executive control tasks by monolingual, bilectal, and bi- or multilingual children; and (iii) the role of comparative bilingualism in children with a developmental language impairment for both the diagnosis and subsequent treatment as well as the possible avoidance or weakening of how language impairment presents.